2020
DOI: 10.3390/su12041651
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Imbalance Between Tourist Supply and Demand: The Identification of Spatial Clusters in Extremadura, Spain

Abstract: The techniques provided by spatial analysis have become a great ally of tourist planning as they allow the carrying out of exhaustive territorial analyses. The greater availability of georeferenced databases together with the more and more extensive use of GIS (Geographic Information Systems) is materialising in the proliferation of studies analysing the distribution patterns of tourist territories. The present study uses these techniques to study the degree of equilibrium in the distribution of places and its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 46 publications
(67 reference statements)
1
26
0
Order By: Relevance
“…According to Rodriguez Rangel and Sanchez Rivero [29], spatial analyses have become a major ally in tourism planning, because they enable exhaustive analyses of the study area. Ruda [30] also emphasizes the advantages of spatial analyses for detecting certain tendencies between neighboring study sites, while also indicating that the results may be unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Rodriguez Rangel and Sanchez Rivero [29], spatial analyses have become a major ally in tourism planning, because they enable exhaustive analyses of the study area. Ruda [30] also emphasizes the advantages of spatial analyses for detecting certain tendencies between neighboring study sites, while also indicating that the results may be unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…An increasingly common method, including in the case of tourism, is Geographic Information Systems (GIS) [29]. One advantage of analyses carried out using GIS tools is that they provide more knowledge of the spatial character of the phenomenon under study.…”
Section: Theoretical Background 21 Spatial Variation In Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…Lascu et al [14] compared the level of tourism in the 17 major regions of Spain and identified the key natural, cultural, and dual attractions using a two-step cluster analysis to ascertain the relative importance of the three types of attractions. Rodriguez and Sanchez [41] claimed that the techniques provided by spatial analysis have become a great ally of tourist planning as they allow exhaustive territorial analyses to be carried out. The authors' present study uses these techniques to study the degree of equilibrium in the distribution of places and its level of occupation in a region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This would support or refute the results of the classical approach. As indicated by various authors [9,23,32,33], this type of technique of mathematical analysis could be very useful to determine whether there are well-defined groups of municipalities that have a similar accommodation supply, and to detect hot and cold spots at a regional scale.…”
Section: Discussionmentioning
confidence: 99%